การแสดงออกของยีนต้านเชื้อรา (เบต้า-1, 3-กลูคาเนสและไคติเนส) ในยางพารา - นันทา เชิงเชาว์ (มหาวิทยาลัยสงขลานครินทร์, 2024)
Hevea brasiliensis leaves inoculated with 1x10' spores/ml of Phytophthora palmivora induced expressions of antifungal genes (beta-1,3- glucanase and chitinase). Seventy-two hour after inoculation, activities of these enzymes were about 2-3 folds higher than those determined in the control leaves. A resistant clone (BPM-24) produced the two enzymes more rapidly and lasted longer than a susceptible clone (RRIM600). In addition, both Hevea clones released total proteins (other proteins including beta-1,3- glucanase and chitinase) at the level and rate similar to the two enzymes. One isozyme (a) and 3 isozymes (a, b, c) of beta-1,3-glucanase were detected in the control leaves of RRIM600 and BPM-24 clones, respectively. While the levels of isozymes a, b, c did not respond to fungal infection, an extra isozyme (d) with the same size in both clones was induced after inoculation. Two isozymes (x, y) and three isozymes (x, y, z) of chitinase were observed in the control leaves of RRIM600 and BPM-24 clones, respectively. The isozymes y and z were increased by fungal infection whereas the isozyme x was decreased after 72 h. of inoculation. The isozyme z which appeared only in the BPM-24 and in the other Hevea resistant clones may be responsible for the resistance of Hevea leaves. Even though the purified RNAs were intact and the cDNA probe did not have problems with homology and labelling, expressions of beta-1,3- glucanase and chitinase genes at the level of RNA were not able to pursue. However, the level of total RNA was shown to express much higher after fungal infection. The increase of total RNA will include the RNAs of the two enzymes because, as reported in other plants, they were induced at the level of transcription.